The reject : community, politics, and religion after the subject - Goh, Irving (Commonalities., 2015)
This title proposes a theory of the reject, a more adequate figure than the subject for thinking friendship, love, community, democracy, the post-secular, and the post-human. Through close readings of Nancy, Deleuze, Derrida, Cixous, Clément, Bataille, Balibar, Rancière, and Badiou, it shows how the reject has always been nascent in contemporary French thought. The recent turn to animals and bare life, as well as the rise of the Occupy movement, also present a special urgency to think the reject today.